Van der knaap disease: A case report - Sardana, Vijay; Bhattiprolu, Rahi Kiran (Indian Journal of Case Reports, 2018)
Van der Knaap disease or megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare autosomal recessive degenerative disorder characterized by megalencephaly, cerebral leukoencephalopathy, and motor deterioration. Most cases reported with this disease in India belong to the Agarwal Community with Consanguinity. Here, we report the case of a 12-year-old boy belonging to this ethnic background presented with a history of delayed motor milestones, ataxia, poor scholastic performance, and seizures. MLC has a benign course and better outcome with life expectancy up to 3rd–4th decade of life. MLC should be included in differentials of macrocephaly and leukoencephalopathy with characteristic magnetic resonance imaging findings. A precise diagnosis helps for better management and to prognosticate its benign course.